THE CRUCIAL ROLE OF MICROORGANISMS IN GLOBAL BIOGEOCHEMICAL CYCLES: MECHANISMS, INTERACTIONS, AND ENVIRONMENTAL IMPLICATIONS - Sardi, Arif (Indonesian Journal of Environmental Sustainability, 2025)
This study outlines the fundamental role of microorganisms including bacteria, archaea, and fungi as primary drivers of global biogeochemical cycles. Data were collected through a comprehensive literature review of various scientific databases, covering recent publications on the contribution of microorganisms to biogeochemical cycles. It explores how microorganisms facilitate the transformation of essential elements such as carbon, nitrogen, phosphorus, and sulfur through various metabolic pathways, ranging from atmospheric gas fixation to the decomposition of complex organic matter. It also highlights environmental factors that influence microbial activity, as well as the ecological and environmental implications of their roles, including contributions to climate regulation, soil fertility, environmental purification, and the impact of anthropogenic activities. A comprehensive understanding of microbial ecology is crucial for predicting and managing environmental systems amid global challenges such as climate change and pollution.